State of the plate: Assessing present and future contribution of fisheries and aquaculture to Hawai'i's food security. (August 2018) - Teneva, Lida T.; Schemmel, Eva; Kittinger, John N.
Abstract: Seafood provides the most important source of protein on the planet, and millions in coastal communities depend on this sector for nutrition, livelihoods, and cultural values. Despite seafood's important role, in many locations the contributions of fisheries and aquaculture to local food security have not been accurately assessed. An overview is provided of current and future contributions of seafood to food security in Hawai'i through metrics using a supply chain approach from hook-to-plate, encompassing production and consumption. Hawai'i's local seafood production is nearly 21, 000 metric tons per year, with 90% sourced from pelagic fisheries, and 6% from reef fisheries. Seafood is a bright spot in the overall Hawai'i food system, providing a relatively higher degree of self-sufficiency than other food sources. Annual local production of seafood in Hawai'i is estimated at 20, 424, 243 ± 1, 958, 488 kg (μ ± SD). Accounting for imports and exports, the total locally available seafood (32, 450, 820 kg ± 1, 571, 905 kg) accounts for about 134 ± 6.5 million meals available every year. Wild-capture fisheries (pelagic and nearshore) in Hawai'i are modeled to be able to meet 45% or less of the growing seafood demand in Hawai'i by 2040, compared to an estimated 55% in 2015. A projected 20% increase in total seafood demand by 2040 would exceed current average annual local production by up to 37%. Improvement in sustainable fisheries, aquaculture, and innovations in value and supply chains are critical if Hawai'i is to improve its seafood security and the food provisioning functions of ocean and coastal environments. Highlights: Seafood contributes substantially to the overall food security in Hawai'i. Until now, methods to assess this critical function were lacking, preventing effective policy. A comprehensive set of metrics on seafood security is presented using a supply chain approach. The Hawaiian archipelago is more self-sufficient on seafood than on other food commodities. Future demand increase will require concomitant investments in increasing production.